Tingkat pengetahuan pegawai PLN Lubuk Pakam tentang kaitan penyakit Periodontal dan kesehatan sistemik - Amalia, Martina; Gultom, Florance Rohani; Hanum, Suryani (TROPHICO: Tropical Public Health J., 2023)
Several studies have revealed that there is a relationship between periodontitis and systemic diseases such as cardiovascular disease, diabetes mellitus, pregnancy, and respiratory disease. This is because periodontal infections act as foci of infection for systemic disease. The study aimed to assess the knowledge level of periodontal disease associated with systemic conditions and diseases in PLN Lubuk Pakam employees. The study aimed to assess the knowledge level of periodontal disease associated with systemic conditions and diseases in PLN Lubuk Pakam employees. The number of respondents was as many as 129 people using total sampling, then respondents filled out the questionnaire. The tests used are validity tests, reliability tests, and descriptive statistical analysis. The description of the level of knowledge of PLN Lubuk Pakam employees about periodontal disease is moderate (64.9%). The description of the level of knowledge of PLN Lubuk Pakam employees about periodontal disease associated with systemic conditions and diseases is less (49.5%). It is necessary to educate or educate the public about the link between periodontal disease and systemic diseases and conditions. The majority level of knowledge of PLN Lubuk Pakam employees about periodontal disease associated with systemic conditions and diseases is less.